Constructing the Tourism Identity of East Flores Through the Fantastic East Flores Program - Giovanni Ximenes Collyn; Centurion Chandratama Priyatna; Aang Koswara (International Journal of Science and Society, 2026)
Modern tourism competition requires destinations to develop clear and distinctive identities. East Flores Regency has long been recognized as a religious tourism destination, particularly through the annual Semana Santa celebration, which attracts large numbers of domestic and international visitors. This study adopts a constructivist qualitative approach using a case study design, with data collected through semi-structured interviews, field and social media observations, and document analysis. It examines the processes of formulation, production, institutionalization, and internalization of East Flores’ identity as a cultural center of the Lamaholot community, alongside its distinctive maritime attractions promoted through the Fantastic East Flores program. The findings show that “Fantastic East Flores” functions as an expansion rather than a replacement of the established religious identity. However, the branding strategy relies more on internal potential mapping than on systematic market analysis. As a result, the implementation of cultural and maritime identity remains inconsistent and continues to be dominated by religious narratives. Although the program has been incorporated into regional policy, its adoption across institutions remains non-binding. Consequently, the new identity has not yet been fully internalized in tourists’ perceptions.